Seed quality improvement applications in black cumin seeds (Nigella sativa L.) - Ekren, Sidika; Paylan, Ismail Can; Gokcol, Adem (Frontiers in Sustainable Food Systems, 2023)
The black cumin plant, which forms the research material, is a plant cultivated in many countries for various purposes. By eliminating the difficulties in seed germination, efficiency can be increased. Applications to improve seed quality include improving harvesting, drying and storage technologies, pre-sowing applications, seed processing and coating technologies. Among these applications, priming applications and seed coating methods occupy an important place. In previous studies on plants from the Ranunculaceae family, various pathogens of plant viruses have been identified. One of the viruses transmitted by seeds of the Ranunculaceae family is Cucumber mosaic virüs (CMV). The aim was to increase germination rates and to achieve early and uniform emergence of black cumin, which has a small seed size and whose embryos also show irregular germination. For this purpose, priming, chemical application and film coating and their combinations were used to determine and recommend the best method.In addition to these studies, black cumin seeds infected with CMV were determined by serological and molecular analysis methods and a series of applications were carried out to eliminate this viral factor from the seeds. As a result of the evaluations, the seeds showed the highest germination rate (91% and 93%, respectively) when priming+polymer+KNO3 and priming+polymer+GA3 were applied. It was found that both polymer application and priming application increased GA3 efficiency. Priming+polymer+GA3 application statistically allowed the seeds to reach the mean germination time (5.87 days) in the shortest time. In contrast, the application of the polymer alone and the applications in combination with the polymer caused the seeds to reach the mean germination time longer than the control. The chemical substances and applications that successfully eliminated the cmv factor in black cumin seeds were determined. It was found that the most successful applications were hot water and ozone applications.